2019
DOI: 10.1109/tit.2018.2878412
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Rate-Distortion Coding of Relevant Information

Abstract: Rate-distortion theory provides bounds for compressing data produced by an information source to a specified encoding rate that is strictly less than the source's entropy. This necessarily entails some loss, or distortion, between the original source data and the best approximation after decompression. The so-called Information Bottleneck Method is designed to compress only 'relevant' information. Which information is relevant is determined by the correlation between the data being compressed and a variable of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…concluding the proof. ∎ This not only serves to complete the proof of the operational interpretation of the quantum IB function given in [15], but is also of independent interest.…”
Section: Convexity Of the Qib Functionmentioning
confidence: 76%
See 3 more Smart Citations
“…concluding the proof. ∎ This not only serves to complete the proof of the operational interpretation of the quantum IB function given in [15], but is also of independent interest.…”
Section: Convexity Of the Qib Functionmentioning
confidence: 76%
“…However, the operational significance of this task remained unclear. Later, Salek et al [15] attempted to give an operational interpretation to the quantum IB function. They showed that it is the optimal asymptotic rate of a certain informationtheoretic task, under the assumption that the quantum IB function is convex.…”
Section: Quantum Information Bottleneckmentioning
confidence: 99%
See 2 more Smart Citations
“…We stop here briefly to remark on the curious resemblance of our function I δ with the so-called information bottleneck function introduced by Tishby et al [13], whose generalization to quantum information theory is recently being discussed [14,15]. Indeed, the concavity and additivity properties of the two functions are proved by the same principles, although it is not evident to us, what -if any-, the information theoretic link between I δ and the information bottleneck is.…”
Section: A Converse Boundmentioning
confidence: 90%